Chronicle of international labor jurisprudence, January / June 2018 - Arias Domínguez, Ángel (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
In the reference period, there are no new “open” or “follow-up” complaints before the Committee on Freedom of Association that affect the Spanish State. Neither reports nos. 384 and 385 (332rd session, Geneva, March 2018) and no. 386 (333rd session, Geneva, June 9, 2018) contain no reference to the Kingdom of Spain. Eight resolutions of the CJEU directly affect Spain. The sentence Carlos Enrique Ruíz Conejero c. Ferroser Servicios Auxiliares, S. A. addresses the legality of the objective dismissal for absenteeism of a worker who stopped going to work due to the consequences of the disability he suffered. In the Jessica Jessica Guisado case c. Bankia, S.A. It was discussed if a pregnant woman could be included in a collective dismissal file. The car Moisés Vadillo c. Alestis Aerospace, S.L. considers inadmissible the pretension of a parent to see his working day reduced by breastfeeding a minor child because the other parent did not work. The car in the Pilar Centeno case c. University of Zaragoza addresses the accommodation to the community order of the exclusion of an interim officer from the process of implementing a program of recognition of professional merits. The judgment of Grupo Norte c. Ángel Manuel Moreira deals with small claims compensation in a fixed-term contract than in an indefinite contract. In the Lucía Montero case c. Madrid Social Care Agency deals with the absence of compensation in a temporary interim contract. In the case INSS c. Crespo Rey is about whether the requirement to contribute for the minimum base in the formalization of a Special Social Security Agreement only for returned Spanish workers is in accordance with the community regulations. The judgment Eva Soraya Checa c. Fogasa discusses whether the payment by Fogasa of the compensation due to the worker that, after the geographical mobility business decision, decides to opt for the indemnified termination of the contract. There are also two other judgments of the Court of Justice that, although they have not been issued in the context of a national process, are referenced because of the relevance they have and the influence they can have on our legal system. In the Vera Egenberger c. Evanglisches Werk für Diakonie discussed the discrimination suffered by a worker employed in a religious institution for not professing any faith. The MB judgment c. Secretary of State for Work and Pensions discussed the discrimination that a worker who changed sex in having access to retirement had suffered at the age that would correspond according to his newly acquired sex. The ECHR has handed down the judgment in López Ribalda and Others. c. Spain, on business viodevigilancia in the place of work without consent of the workers and without knowledge of the representatives. Although the hidden video surveillance system did comply with the margins of legality established in the internal legal order, the ECHR understands that there has been a violation of the European Convention on Human Rights.